Proteome profiling of methyl jasmonate elicitation of Maytenus ilicifolia in vitro roots reveals insights into sesquiterpene pyridine alkaloids - Santos, Vânia A. F. F. M. dos [UNESP]; Coppede, Juliana da Silva; Dias, Nathalia Batista; Pereira, Ana Maria Soares; Palma, Mario Sergio [UNESP]; Furlan, Maysa [UNESP] (Springer Nature, 2022)
Maytenus ilicifolia (Celastraceae) is an important medicinal plant widely used in Brazil and a rich source of sesquiterpene pyridine alkaloids (SPAs) with relevant biological activities. They exhibit great chemical diversity and high structural complexity, and show accumulation in very low concentrations. Thus, to determine whether in vitro cultured adventitious roots of M. ilicifolia could provide alternative sources for the production of these compounds, the accumulation of SPAs ilicifoliunine A and aquifoliunine E-I, as well as the time of production and the content of these alkaloids were evaluated using methyl jasmonate (MeJA) as an elicitor. The results showed the accumulation ilicifoliunine A and aquifoliunine E-I and an increase in the contents of these alkaloids when elicited with MeJA at 7 and 28 days, respectively. To characterize and identify the proteins present in the enzymatic system and contribute to the understanding of the metabolic pathways involved in the biosynthesis of SPAs, was carried out in vitro proteomic profiling of adventitious roots elicited and non-elicited with MeJA. The shotgun proteomic analyses led to the identification of important proteins involved in the biosynthetic pathway of SPAs, including germacrene A synthase, β-eudesmol synthase, and L-aspartate oxidase. Additionally, many proteins that participate in the biosynthesis of other alkaloids (e.g., tropane, pyrrolidine, terpenoid indole, and isoquinoline) and phenylpropanoids have been identified. In conclusion, the study report for the first time, proteins involved in the biosynthetic pathway of SPAs by using the adventitious roots in vitro system of M. ilicifolia and a shotgun proteomic approach.
Keywords: Celastraceae; In vitro adventitious roots; Maytenus ilicifolia; Methyl jasmonate; Sesquiterpene pyridine alkaloids; Shotgun proteomic